Տուբերկուլոզ/ՄԻԱՎ համակցված ախտաբանությամբ հիվանդների կյանքի որակը - Ն. Գ. Ազիզյան (Հայաստանի ԳԱԱ)
Оценка качества жизни пациентов с ВИЧ-ассоциированным туберкулезом (ТБ) важна при разработке стратегии и реализации интервенционных программ по лечению, уходу и поддержке людей, живущих сВИЧ и ТБ. В данном исследовании мы сравнили качество жизни ВИЧ-позитивных и негативных пациентов с ТБ.Assessing the health related quality of life among TB/HIV co-infected people is of great importance in designing strategies and implementing interventional programs on treatment care and support to people living with HIV and tuberculosis. In this study we have compared the quality of life of HIV positive and negative Armenian patients with TB.
Keywords: Medicine; Tuberculosis